Historical dictionary of Pakistan - Burki, Shahid Javed (Historical dictionaries of Asia, Oceania, and the Middle East, 2015)
"This fourth edition of Historical Dictionary of Pakistan covers its history through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has over 700 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture"--eCIP data